Group Conflict and Political Mobilization in Bahrain and the Arab Gulf : Rethinking the Rentier State - Gengler, Justin (Book collections on Project MUSE., 2015)
The oil-producing states of the Arab Gulf are said to sink or swim on their capacity for political appeasement through economic redistribution. Yet, during the popular uprisings of the Arab Spring, in Bahrain and all across the Arab Gulf, ordinary citizens showed an unexpected enthusiasm for political protest directed against governments widely assumed to have co-opted their support with oil revenues. Justin Gengler draws on the first-ever mass political survey in Bahrain to demonstrate that neither is the state willing to offer all citizens the same bargain, nor are all citizens willing to ac.